Reactive powder concrete reinforced with nano SiO2-coated TiO2. (1st September 2017) - Han, Baoguo; Li, Zhen; Zhang, Liqing; Zeng, Shuzhu; Yu, Xun; Han, Bing; Ou, Jinping
Graphical abstract: Highlights: Nano SiO2 -coated TiO2 is used to reinforce reactive powder concrete (RPC). Inclusion of nano SiO2 -coated TiO2 into RPC leads to increase of 87%/6.69 MPa in flexural strength. Nano SiO2 -coated TiO2 has pozzolanic effect and decreases the amount of CH. Coating of nano SiO2 at surface of TiO2 is beneficial for dispersion of nano fillers in matrix. Abstract: Nano SiO2 -coated TiO2 (NSCT) is used to reinforce reactive powder concrete (RPC). The reinforcing mechanisms of NSCT are investigated through thermogravimetry (TG) analysis, X-ray powder diffraction (XRD) analysis, elemental analysis and scanning electron microscope (SEM) observation. The mechanical strengths of the NSCT reinforced RPC (NSCTRRPC) at different curing ages manifest significant increases, especially flexural behaviors. The flexural and compressive strengths of NSCTRRPC at age of 28 d achieve increases of 87%/6.69 MPa and 12.26%/12.2 MPa with respect to RPC without NSCT, respectively. TG analyses suggest that acceleration of cement hydration caused by nucleus effect plays a dominant role in the early days. XRD analyses manifests the NSCT decreases the amount of CH crystals in matrix. This suggests that the NSCT has the pozzolanic effect. In addition, element analysis is indicative that NSCT is uniformly distributed inside the matrix to make the cement matrix more compact, which is in consistent with SEM observations. It is therefore concluded that coating of nano SiO2 at the surface of TiO2 is beneficial for the dispersion of nano fillers in matrix and the pozzolanic effect, thus modifying the microstructures and the mechanical property of RPC.